Study of nutritional status of children attending OPD at a tertiary-care hospital in eastern region of Nepal - Rajbandari, RM; Lewis, O; Singh, R; Smith, S (Health Renaissance, 2011)
Background: Prevalence of malnutrition is high in Nepal. Early intervention improves outcome of children. Objectives: To study the occurrence of the malnutrition in under five children coming to the OPD at BPKIHS and to find out the age group & sex most severely affected by malnutrition. Methods: A descriptive cross sectional hospital-based study was carried out from 2003-04. 500 children aged 1-5 years were taken as a sample The children needing emergency care were excluded. The Indian Academy of Pediatrics (IAP) and WHO classification were used for grading malnutrition. Results: Total patient were 500 aged 1-5 yrs group. Total malnutrition cases were 124 with a prevalence of 24.8% .Malnutrition was highest in 3-4 years group (33.3%). Conclusion: It is found that total malnutrition cases were about 24.8%.A more elaborate and community based study would help to find prevalence of malnutrition in children of Eastern Nepal. Keywords: nutritional status; PEM; affected by malnutrition DOI: http://dx.doi.org/10.3126/hren.v9i2.4982 Health Renaissance 2011: Vol.9 (No.2): 102-105